An Innovative Thinking on the Effect Evaluation and System Improvement of Senile Monitoring - A, Runa (International Journal of Social Sciences and Public Administration, 2024)
China is preparing for its rapidly aging population and implementing an effective system of elder guardianship. Due to policies such as the one child policy and longer life expectancies, in combination with improved economic conditions, this demographic shift has put great pressures on social, legal and healthcare systems. In this paper, the authors investigate the development of elder guardianship in China, its present struggles as well as possible policy pathways.The current study aims to evaluate the efficacy of elder guardianship in China using an extensive literature review and incorporating theoretical discussions into legal analyses. Through comparisons with international guardianship models, foreign best guardianship practices to learn from the Chinese situation to find out. We reviewed case studies of efforts to reform elder care, both in community-based and governmental health strategies.The results presented in this article reinforce that although the Civil Code of PRC (2021) may be a significant step forward towards a more legal frameworking concerning elder guardianship, there are still challenges to be faced relating to the variety in law enforcement, oversight, and public awareness. Moreover, the transition to nephology nuclear living has also exacerbated the guardianship accommodate system. In addition to this, a key aspect relates to the reform required in pension and social security policies for the elderly population.The paper concludes that the guardianship system in China may improve by combining a family model with a public one, developing community-based elder care, and utilizing technology for monitoring. Suggestions also focus on strengthening legal frameworks, enhancing guardian oversight and encouraging elder care service innovation to better the quality of lives of those under guardianship.The authors of the study conclude that China’s progress in elder guardianship has been commendable but there is still a long way to go, especially as far as legal issues are concerned and socio-administrative care services. Future studies in China need to explore more culturally distinctive and multifaceted modes of guardianship that are better fitted for the country’s burgeoning older population.